Functional Cross-Antagonism between Transcription Factors FLI-1 and EKLF - Joëlle Starck; Nathalie Cohet; C. Gonnet; Sandrine Sarrazin; Zina Doubeikovskaia; Alexandre Doubeikovski; Alexis Verger; Martine Duterque‐Coquillaud; François Morlé (2003)
FLI-1 is an ETS family transcription factor which is overexpressed in Friend erythroleukemia and contributes to the blockage of differentiation of erythroleukemic cells. We show here that FLI-1 represses the transcriptional activity of the beta-globin gene promoter in MEL cells and interacts with two of its critical transactivators, GATA-1 and EKLF. Unexpectedly, FLI-1 enhances the stimulating activity of GATA-1 on a GATA-1-responsive promoter but represses that of EKLF on beta-globin and an EKLF-responsive artificial promoters. This repressive effect of FLI-1 requires the ETS DNA binding domain and its association with either the N- or C-terminal domain, which themselves interact with EKLF but not with GATA-1. Furthermore, the FLI-1 ETS domain alone behaves as an autonomous repression domain when linked to the Gal4 DNA binding domain. Taken together, these data indicate that FLI-1 represses EKLF-dependent transcription due to the repression activity of its ETS domain and its indirect recruitment to erythroid promoters by protein-protein interaction with EKLF. Reciprocally, we also show that EKLF itself represses the FLI-1-dependent megakaryocytic GPIX gene promoter, thus further suggesting that functional cross-antagonism between FLI-1 and EKLF might be involved in the control of the erythrocytic versus megakaryocytic differentiation of bipotential progenitors.